Auditoría Tributaria para medir el riesgo fiscal en la Empresa Proveedora de Insumos Médicos P.I.M.; Riobamba período 2017 - Alcívar Cabrera, María José (2019)
P.I.M is an entity with 22 years of experience has been achieved positioner with force in the field of trade in medical supplies at the provincial level, P.I.M It has undergone a process of review or determination on the part of the tax administration as well as not been subject to sanctions, fines, and surcharges, nor has done over the last few years a preventive tax audit by external auditors. Tax obligations that own P.I.M. found in the Single Register of the Taxpayer RU.C also, it is subject to the legal provisions of the regulations a year of study LORTI, its rules, and resolutions issued by the governing body. Through the development of this audit seeks to demonstrate that in companies and in particular the entity studied, applying a tax audit determines the level of financial risk existíng in the substance, in addition to recognizing measures that may decrease this risk and avoid future sanctions on the part of the tax administration. The results of the audit determined that the entity does not comply fully with the regulations is not reflect the reasonableness of the ínfomation faithfully, because there are differences, tangible or intangible, increasing the level of tax risk, this indicates that the differences alter the income tax, therefore; the P.1M is facing a high level of financial risk on the part of the Tax Administration (S.R.I.).